2015
DOI: 10.1016/j.homp.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of Lycopodium clavatum 30CH on experimental model of paracetamol-induced liver damage in rats

Abstract: Lyc 30c exerted a moderate hepatoprotective effect on acute Pct-induced hepatitis, mainly shown by a histological decrease in necrosis and inflammatory foci, preserved glycogen and other 1,2-glycols in zone 3 and reduced serum levels of ALT and AST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Our results, proving the antioxidant potential of Lyc, are in line with a previous study of a Lyc-enhanced antioxidant response in aging mice [42]. Lyc has also been reported to protect against cognitive [43], inflammatory [24,25] and neuronal [36,42] damage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results, proving the antioxidant potential of Lyc, are in line with a previous study of a Lyc-enhanced antioxidant response in aging mice [42]. Lyc has also been reported to protect against cognitive [43], inflammatory [24,25] and neuronal [36,42] damage.…”
Section: Discussionsupporting
confidence: 92%
“…It has been a popular remedy in traditional Chinese and homeopathic medicines for centuries [18,19,20]. It has also been reported to possess anti-cancer [21,22], analgesic [23] and anti-inflammatory [24,25,26] properties. Lycopodium alkaloids, such as quinolizine or pyridine and α-pyridone-types, have been reported to possess acetylcholinesterase inhibition activity.…”
Section: Introductionmentioning
confidence: 99%
“…Serum AST and ALT liver function biomarkers are inversely related to the severity of liver damage [ 66 68 ]. We found that both ALT and AST levels were significantly higher in the 2/3 PH group mice than in the sham group mice on day 2 and day 4 after 2/3 PH and that RD treatment reversed these changes.…”
Section: Discussionmentioning
confidence: 99%
“…Our research selected a homeopathic solution to be investigated, as this type of treatment has been effectively used in several managements, fighting the disease itself or the effects caused by the conditions. Several studies demonstrate the effectiveness of homeopathy in the treatment of multiple sclerosis 21 ; chronic prostatitis due to radiation 22 ; acute radiodermatitis 23 ; cancerous lesion 24 ; xerostomia 25 , DNA damage, and oxidative stress 26 ; and as hepatoprotective 27 .…”
Section: Discussionmentioning
confidence: 99%